Perception of mixed modulation for single components in harmonic complex for high modulating frequencies - KIN, M. J.; DOBRUCKI, A. B. (Archives of Acoustics, 1998)
Results and problems of perception of mixed modulation in a harmonic multitone are discussed. The experimental research was done for higher modulating frequencies (70 and 200Hz) and a 5-harmonics complex with fundamental frequency of 256Hz. The results indicated that for a modulating frequency of 70Hz, the perception of frequency modulation in the presence of the threshold values of the amplitude modulation is different from the perception of amplitude modulation in the presence of the threshold values of the frequency modulation. This means clearly that there are two mechanisms of the perception for these kinds of modulation.